DISCIPLINE CHARACTER EDUCATION TO AVOID STUDENT MORAL DEGRADATION - Rofiatul Istiqomah; Anita Fitriya; Finadatul Wahidah; Siti Hamidahtur Rofi’ah; Umah Amrela; Ratri Kurnia Pratiwi; Evi Maulidah; Badrun Fawaidi (International Conference on Humanity Education and Society (ICHES), 2023)
This research aims to find out the strategy at SMPN 2 Jember to avoid problems regarding Moral Degradation. The approach used is a qualitative approach with descriptive methods. Data collection techniques used in this study were interviews, observation, and documentation. The results of this study indicate that the cultivation of student discipline begins when new students enter the school, namely through MOS (Student Orientation Period) activities. In this activity, students were also introduced to the rampant problem of Moral Degradation in Indonesia and the negative impacts caused by this moral Degradation. From the results of this study, researchers were also able to find out the applicable system for dealing with children who violated it, namely by using a point system.